“The school that I seek, the school that I offer”: Contents and rationalities of the educational offer of the Chilean school market - Oyarzún Maldonado, Cristian José (Education Policy Analysis Archives, 2021)
Chile's school system is a unique social space for analyzing the enactment of market policies and accountability. The article presents research that examines the contents and rationalities of the educational offer of schools in Santiago de Chile. The educational offer was operationalized through external advertising posters that, following S. Ball's theory, constitute fabrications, i.e. images or versions of schools, which may or may not be true, and whose purpose is to respond to the disciplines of the market. In the methodological sense, a mixed sequential approach was used that, in the first quantitative phase, allowed to analyze predictor variables of the use of posters in a population of schools and identify prototypical posters. Then, in the second qualitative phase, the sociocultural interpretation that managers and families made of the prototypical posters was investigated. The integration of quantitative and qualitative findings suggests that: (a) the assistance grant has a significant influence on suppliers' business conduct and positioning strategies; (b) the consolidation of a performative quasi-market induces suppliers to seek to attract a disadvantaged audience in socio-economic and academic terms; (c) educational actors develop arguments for differentiated student profiles according to school types, justifying dynamics of self-segregation; and (d) state program’s and recognitions are recontextualized as advertising inputs and means to certify the educational offering.